Circular Economy Perspective of Hifdz Al-Bi'ah Through the Utilization of Shell Waste as Raw Material for Decorative Products - Koyyimah, Jazirotudiinil; Fahrurrozi, Fahrurrozi (Perisai : Islamic Banking and Finance Journal, 2024)
Shell waste, which is often considered a waste material, has great potential to be processed into handicraft products with economic value. Through an environmentally friendly processing process, the waste can be converged into goods that are not only in demand in the market, but also encourage public awareness of the importance of recycling and environmental maintenance. This research aims to explore how often overlooked waste can be processed into decorative items that not only reduce negative impacts on the environment, but also create new economic opportunities for the community. The research method used is qualitative with a descriptive approach, involving observation and interviews with handicraft business actors. The results of the study show that the use of shell waste can increase public awareness of the importance of waste management and environmental protection. In addition, this research highlights the importance of training and innovation in creating attractive and value-added products. Thus, this research makes a significant contribution to the development of a sustainable and environmentally friendly craft industry, as well as encouraging the adoption of circular economy principles in various sectors. In conclusion, the use of shell waste not only meets economic needs, but also contributes to environmental sustainability and improving people's quality of life.